Handling Violence in Legislation in Indonesia - Heri Tahir; Ririn Nurfaathirany Heri; Hairul Saleh Satrul (Cita konsultindo, 2025)
Violent crimes are a form of legal violation that have multidimensional impacts on victims, perpetrators, and society. Violence not only causes physical and psychological suffering but also creates social instability, collective fear, and economic and psychological burdens. The characteristics of violent crimes in Indonesia reflect socio-cultural and legal complexities that require a holistic response strategy. With a high prevalence of gender-based violence and high levels of underreporting, victim protection, legal outreach, and law enforcement reform are crucial to reducing the number of violent crimes. This research uses legislative, conceptual, and comparative approaches. The research is related to the prevention and handling of violence, so it is hoped that this research can provide considerations for policymaking related to the prevention and handling of violence in the future. In other words, this research can also serve as ius contituendum. Before the specific regulations on sexual violence, the Criminal Code, the ITE Law, and the Pornography Law were in effect. Then, Regulation of the Minister of Education, Culture, Research, and Technology No. 55 of 2024 concerning the prevention and handling of sexual violence that favors victims came into effect. The ministerial regulation requires every educational institution to establish a PPKS Task Force, provide holistic services for victims, and impose administrative sanctions on perpetrators. The existence of these various special regulations creates challenges, the solution of which lies in harmonizing norms and implementing the lex specialis principle, where the TPKS Law is positioned as the primary and comprehensive special law.